2015
DOI: 10.1615/intjmedmushrooms.v17.i3.30
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ganoderma lucidum (Higher Basidiomycetes) Extracts on the miRNA Profile and Telomerase Activity of the MCF-7 Breast Cancer Cell Line

Abstract: Ganoderma lucidum is a medicinal higher Basidiomycetes mushroom that exerts anticancer effects through several different mechanisms. This study investigated the effects of G. lucidum on the telomerase activity and microRNA (miRNA) profiles of MCF-7 cells. According to the cytotoxicity results, the G. lucidum ether extract exhibits the highest cytotoxic potency; therefore it was chosen for the subsequent telomerase activity assay and miRNA profiling. The telomerase activity observed in the cells treated with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Most of these miRNAs have been previously reported in at least one publication associated with cancer, some of which are well-studied tumor suppressors, including has-mir-133b, and hsamir-139, or contribute to cell invasion, such as hsa-mir-301b [28,29] hsa-mir-1247 was newly found to be a prognostic marker in pancreatic cancer as a suppressor [28], and hsa-mir-1258 targets heparanase (HPSE) to suppress breast and non-small cell lung cancer [30,31]. hsa-mir-1269a, hsa-mir-3687, and hsa-mir-3648 were also newly identified to be involved in cancer development [32][33][34], but their molecular mechanisms in cancers need to be researched further.…”
Section: Data Collection and Overall Evaluation Before Differential Ementioning
confidence: 99%
“…Most of these miRNAs have been previously reported in at least one publication associated with cancer, some of which are well-studied tumor suppressors, including has-mir-133b, and hsamir-139, or contribute to cell invasion, such as hsa-mir-301b [28,29] hsa-mir-1247 was newly found to be a prognostic marker in pancreatic cancer as a suppressor [28], and hsa-mir-1258 targets heparanase (HPSE) to suppress breast and non-small cell lung cancer [30,31]. hsa-mir-1269a, hsa-mir-3687, and hsa-mir-3648 were also newly identified to be involved in cancer development [32][33][34], but their molecular mechanisms in cancers need to be researched further.…”
Section: Data Collection and Overall Evaluation Before Differential Ementioning
confidence: 99%
“…A literature search on miR-3687 retrieved only a few articles related to malignant neoplasia. One study has referred to invasive ability and poor prognosis of oesophageal cancer, another to increasing local recurrence of conjunctival melanoma and a third to telomerase activity of a breast cancer cell line (30,33,34). The present study was the first to investigate both miR-3687 as a differentially expressed miRNA in BSCCE and its putative target genes in oesophageal carcinoma.…”
Section: Discussionmentioning
confidence: 82%
“…By microRNA profiling, we have shown that several miRNAs, some of which are associated with different clinical-pathological characteristics of breast cancer, such as stemness, invasion and chemoresistance, could be differentially expressed after AHCC administration. For example, miRNAs miR-92a, miR-181a, miR-183 Ã , miR-335, miR-497, miR-500a, miR-720, and miR-1285 [53][54][55][56][57][58][59][60] (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%